2006
DOI: 10.1103/physrevb.73.125107
|View full text |Cite
|
Sign up to set email alerts
|

Normalized-lifetime thermal-lens method for the determination of luminescence quantum efficiency and thermo-optical coefficients: Application toNd3+-doped glasses

Abstract: We present a new method based on thermal lens ͑TL͒ technique to determine the fluorescence quantum efficiency, , and thermo-optical coefficients of fluorescent materials. These parameters can be obtained from the linear dependence of the TL signal with the experimental lifetimes of a set of samples with different luminescent ion concentrations. The method was applied in Nd 3+ -doped materials ͑Q-98 Phosphate, fluorozirconate, and fluoroindate͒. The obtained values are in agreement with those determined by othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 36 publications
3
43
1
2
Order By: Relevance
“…8͒ as reported in glass matrices. 39,40 This is supported by the existence of Nd 2 O 3 nanocrystals in the FIG. 7.…”
Section: Discussionmentioning
confidence: 75%
“…8͒ as reported in glass matrices. 39,40 This is supported by the existence of Nd 2 O 3 nanocrystals in the FIG. 7.…”
Section: Discussionmentioning
confidence: 75%
“…19 The fluorescence quenching effect is mainly due to ion-ion energy transfer processes involving nonradiative paths and is favored for high ionic concentrations. 28,29 This effect, less pronounced for Nd:YAlB glasses than for other borate glasses, might be attributed to some extent of substitution of Nd 3+ by Y 3+ preventing the Nd 3+ cluster formation. 17 For YAB crystal, low contents of rare-earth ions can be incorporated in Y 3+ sites without causing any distortion, but as the concentration is raised, increasing disorder leads to an emission band broadening ͑ϳ40 nm͒ and to a redshift of the emission peak from 1064 to 1062 nm.…”
Section: B Photoluminescence and Excited State Lifetimesmentioning
confidence: 95%
“…In this sense, it is important to note that a main common feature of Nd 3+ doped materials, independently of the excitation wavelength, is that all emission bands originate from the 4 F 3/2 metastable state. 28 In other words, the relationship between ͓see Eq. ͑1͔͒ and has a simple form, 29 being given by =1 − ͗ em ͘ exc −1 , where ͗h em ͘ and h exc are the average emission and excitation energies, respectively.…”
Section: Thermo-optical Propertiesmentioning
confidence: 99%
“…Jacinto et al [148] have reported a relatively simple method to determine emission quantum efficiency (η) and thermo-optical coefficients. This method does not require a direct comparison between the luminescence properties of reference and sample and is based on the normalized-lifetime thermal lens (TL) technique.…”
Section: Glasses Leds Oleds and Crystalsmentioning
confidence: 99%